Psychological well being karyawan produksi: Adakah peranan transformational leadership dan gratitude? - Firdiansyah; Diah Sofiah; Yanto Prasetyo (INNER: Journal of Psychological Research, 2023)
This study aims to explain "The Relationship of Transformational Leadership and Gratitude with Psychological Well-Being in Production Employees of PT. Kasa Husada Wira East Java”. This research is motivated by problems in the use of transformational leadership and gratitude for each employee, especially in Indonesia, for psychological well being. Subjects in this study amounted to 68 people. The results of the hypothesis test obtained a correlation coefficient value of 0.738 with a significance of p = 0.000 (p <0.01) for the transformational leadership variable, while for the gratitude variable a correlation coefficient value of 0.510 was obtained with a significance of p = 0.000 (p <0.01), p. this indicates that there is a very significant positive relationship between transformational leadership and psychological well-being as well as gratitude there is also a very significant relationship with psychological well-being so that both hypotheses are accepted. So that the higher the value of transformational leadership and gratitude, the higher the psychological well being. Keywords : transformational leadership, gratitude, psychological well being, employees, spearman rho Penelitian ini bertujuan untuk menjelaskan “Hubungan Transformational Leadership dan Gratitude dengan Psychological Well-Being pada Karyawan Produksi PT. Kasa Husada Wira Jatim”. Penelitian ini di latar belakangi oleh permasalahan pada penggunaan transformational leadership serta gratitude pada setiap karyawan khususnya di Indonesia terhadap psyhcological well being. Subjek dalam penelitian ini berjumlah 68 orang. Hasil uji hipotesis memperoleh nilai koefisiensi korelasi sebesar 0,738 dengan signifikansi p = 0,000 (p < 0,01) untuk variabel transformational leadership, sedangkan untuk variabel gratitude diperoleh nilai koefisiensi korelasi sebesar 0,510 dengan signifikansi p = 0,000 (p < 0,01), hal ini menandakan bahwa adanya hubungan positif yang sangat signifikan antara transformational leadership dengan psychological well-being begitu pula gratitude juga terdapat hubungan yang sangat signifikan dengan psychological well-being sehingga kedua hipotesis tersebut diterima. Sehingga semakin tinggi nilai transformational leadership dan gratitude maka akan semakin tinggi pula psychological well being. Keywords : transformational leadership, gratitude, psychological well being, karyawan produksi, spearman rho